Forming Preachers: An Examination of Four Homiletical Pedagogy Paradigms - Clark, E. Trey (Religions, 2024)
Teaching preaching effectively in the twenty-first century requires instructors to engage a multiplicity of pedagogical approaches. Unfortunately, there is a paucity of homiletical literature that surveys diverse pedagogical paradigms and practices directly related to preaching. This article takes a step toward filling this void. Specifically, the author argues that embracing varied preaching pedagogical paradigms and practices is essential to foster a more holistic, contextually sensitive, and liberative approach to the formation of preachers. The first part of the article examines three major contemporary homiletical pedagogical approaches that attend to the formation of preachers in interrelated yet distinct ways: teacher-centered, learner-centered, and learning-centered preaching pedagogy. In the second section, building on place-based educational theory, a new paradigm is explored that the author calls place-centered preaching pedagogy. To explicate this paradigm, the article briefly considers four homileticians who, in different ways, reflect aspects of this pedagogy in their teaching: HyeRan Kim-Cragg, Frank A. Thomas, Richard W. Voelz, and Leah D. Schade. The third section offers an assessment of place-centered preaching pedagogy by examining its strengths, weaknesses, and areas for future research. The article ends with a conclusion that revisits the primary aims of the essay and calls for further exploration of the subject.